Cost Effectiveness Analysis (CEA) Strategi Terapi Anemia pada Pasien Penyakit Ginjal Kronis - Nurfina Dian Kartikawati; Tri Murti Andayani; Dwi Endarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Chronic kidney disease (CKD) is a condition in which the kidneys are unable to maintain a fluid balance of metabolic waste that is progressive, irreversible, and takes place slowly. Anemia is a complication of CKD that contributes to morbidity, mortality, and quality of life of patients, as well as greater costs of care. This study aims to evaluate the differences in the effectiveness and cost of anemia therapy with epoetin in patients with chronic kidney disease. The study was conducted in an analytical-observational manner with a retrospective cohort design from the provider's perspective. The sample used was CKD patients with anemia who met the inclusion criteria for the period January - December 2020, data were taken from medical records and patient financial recapitulation. Statistical analysis was carried out on the effectiveness of anemia therapy with epoetin based on the achievement of clinical outcomes of increasing Hb values within 3 months and financing calculated based on direct medical costs. A total of 113 patients met the inclusion criteria, consisting of 96 patients in the epoetin alpha group and 17 patients in the epoetin beta group. The percentage of achieving therapeutic targets in the epoetin beta group was higher (11.76%) than in the epoetin alfa group (10.42%). The average increase in Hb in the EPO beta group was higher than in the EPO alpha group. The cost of epoetin for anemia treatment in the beta epoetin group (Rp 1,005,365) was lower than the epoetin alfa group (Rp 1,017,188). The ICER value obtained was IDR -125,966, indicating a cost savings of IDR 125,966 to increase 1% of the achievement of therapeutic targets for Hb values >10 g/dl. The cost of therapy with EPO beta is lower than EPO alpha and the achievement of Hb therapy targets is better in EPO beta than EPO alpha.